Featuring Knowledge as the Means to the Essence of Creation: An Islamic Exposition - Usman Jimoh Muhammad (Al-Misbah (Jurnal Islamic Studies), 2021)
The paper dwells on the crucial role of knowledge in the life of man. Knowledge is presented as a means to realization of the purpose for which man came into the world which is “to worship God. Knowledge as classified in the paper has two branches of which are Fard ayn (knowledge which is incumbent on everyone) and Fard Kifayah (knowledge which is needed to be acquired by some and not everyone). The paper buttresses the necessity of the two categories of knowledge towards attaining the desire to worship God accordingly. Viewing the fact that after the creation of man, knowledge was the first endowment given to man and the first promise made to him on his way to the earth one is bound to believe in the necessity of knowledge towards realisation of the purpose of creation. Relying on the fact that the first revelation emphasises on the search for knowledge; the stipulation for acquisition of knowledge before exhibition of actions coupled with the relevance of professional knowledge to ease of life and worship, it is justifiable to conclude that knowledge is a means towards realization of the essence of creation. This assertion is greatly reinforced with the aid of relevant Qur’anic text and prophetic traditions. The paper recommends that parents should ensure that their children receive sound knowledge of Islam as well as any other aspects of the knowledge that is Fard kifayah.